O conceito de trabalho nos manuscritos econômico-filosóficos de Karl Marx - Farias, Tarcisio Fagner Aleixo (2010)
This study aims to understand the conceptual web that permeates the notion of labor by Marx in the Economic and Philosophical Manuscripts. We relate the notion of labor, as productive human activity, to three other concepts: human essence, strangeness and freedom. In the relationship between labor and human essence labor shall be viewed, generally, as the activity of the metabolism between man and nature, and in that sense it is the peculiar brand of men to the animal kingdom, because only they have the ability to create their own world according to their will. The relationship between labor and strangeness intends to show particular forms of labor in what private property prevails, especially to describe the modern conditions of life. The last part inserts a problem to healthy understanding of Marx's thought, is also the labor that creates possibilities of human emancipation, thus relating directly to the concept of freedom, seen as an overcoming of estrangement and, at the same time, the realization of the human essence. The three concepts are therefore complementary and indispensable to understanding the meaning of human history in Marx.